Factors influencing the adoption of e-payment: an empirical study in Malaysia / Intan Syafinaz Mat Shafie ...[et al.] - Mat Shafie, Intan Syafinaz; Mohd Yusof, Yuslina Liza; Mahmood, Ainun Nadzirah; Mohd Ishar, Nor Irvoni; Jamal, Hartini Zuhaila; Abu Kasim, Noor Hidayatul Aini (Faculty of Business and Management, Universiti Teknologi MARA, 2018)
This study examines the antecedents of the factors that influence customers to adopt the electronic payment system while making payments. Payment is the one of the element to complete the transaction while making payment. Due to the development of E-commerce, e-payment systems have been introducing. So, the use of electronic payment systems is being increasing day by day for people to complete their task quickly ineffective way. The result of the study shows that there is a relationship between dependent variables (effort expectancy and social influence) and independent variable (Adopton of e-payment). However, other variables (culture, perceived security and performance expectancy) were not significant with adoption of e-payment. Therefore, the study approves effort expectancy and social influence has a significant relationship with adoption of e-payment. Therefore, companies today that do business using electronic payment system as the medium to complete the transaction must focus more on this two variable to increase the number of people use this payment system. The increasing the number of people use this payment system will contribute to excellent result for e-commerce because e-payment system is one of the factor e-commerce becomes successful and it will give good impact to our nation’s economy.